FIELD, TEMPERATURE, AND ANGLE DEPENDENCE OF THE CRITICAL-CURRENT DENSITY IN BI2SR2CACU2O10/AG RIBBONS - Dhalle, M; Cuthbert, M; Cohen, L; Perkins, G; Caplin, A; Yang, M; Grovenor, C; Dou, S; Liu, H; Hu, Q; Wolf, E; Lu, F; et al. (Kluwer Academic Publishers-Plenum Publishers, 1995)
Current-voltage characteristics of high-critical-current Bi2Sr2CaCu2O10/Ag ribbons were measured using both transport and magnetization techniques. The slope of these curves changes with magnetic field and temperature in a way very similar to the observed jc(H, T) behavior. This correspondence between the critical current and the slope of the I-V characteristics can be explained within the thermally activated flux creep framework. The dependence of jc on the angle between field and ribbon is compared to the existing intrinsic anisotropy models. © 1995 Plenum Publishing Corporation.